Changes in Gastric Corpus Microbiota With Age and After Helicobacter pylori Eradication: A Long-Term Follow-Up Study - Shin, Cheol Min; Kim, Nayoung; Park, Ji Hyun; Lee, Dong Ho (Frontiers in Microbiology, 2021)
Helicobacter pylori infection changes gastric microbiota profiles. However, it is not clear whether H. pylori eradication can restore the healthy gastric microbiota. Moreover, there has been no study regarding the changes in gastric microbiota with aging. The objective of this study was to investigate the changes in gastric corpus microbiota with age and following Helicobacter pylori eradication. Changes in corpus mucosa-associated microbiota were evaluated in 43 individuals with endoscopic follow-up > 1 year, including 8 H. pylori-uninfected and 15 H. pylori-infected subjects with no atrophy/metaplasia by histology and pepsinogen I/II ratio > 4.0; 17 H. pylori-infected subjects with atrophy/metaplasia and pepsinogen I/II ratio < 2.5; 3 subjects with atrophy/metaplasia, no evidence of active H. pylori infection, negative for anti-H. pylori Ig G antibody testing, and no previous history of H. pylori eradication. Successful H. pylori eradication was achieved in 21 patients. The gastric microbiota was characterized using an Illumina MiSeq platform targeting 16S rDNA. The mean follow-up duration was 57.4 months (range: 12-145 months), and median follow-up visits was 1 (range: 1-3). Relative abundance of Lactobacillales and Streptococcus was increased with atrophy/metaplasia. In H. pylori-uninfected subjects (n = 8), an increase of Proteobacteria (Enhydrobacter, Comamonadaceae, Sphingobium), a decrease of Firmicutes (Streptococcus, Veillonella), Fusobacteria (Fusobacterium), Nocardioidaceae, Rothia, and Prevotella, and a decrease in microbial diversity were observed during the follow-up (p trend < 0.05). In 10 of 21 subjects (47.6 %), H. pylori eradication induced restoration of microbial diversity; however, a predominance of Acinetobacter with a decrease in microbial diversity occurred in 11 subjects (52.3 %). The presence of atrophy/metaplasia at baseline and higher neutrophil infiltration in the corpus were associated with the restoration of gastric microbiota after successful eradication, whereas a higher relative abundance of Acinetobacter at baseline was associated with the predominance of Acinetobacter after H. pylori eradication (p < 0.05). To conclude, in H. pylori-uninfected stomach, relative abundance of Proteobacteria increases, relative abundance of Firmicutes and Fusobacteria decreases, and microbial diversity decreases with aging. H. pylori eradication does not always restore gastric microbiota; in some individuals, gastric colonization by Acinetobacter species occurs after anti-Helicobacter treatment.